Comportamento eletrostático em interface líquido-sólido: estratégias para detecção de fluxo de líquidos - Campo, Yan Araujo Santos da (2024)
Although known since ancient times, triboelectricity is a phenomenon whose fundamental causes are not yet fully understood, especially in liquid-solid interfaces. Significant efforts have initiated studies on electrostatic charging at these interfaces, particularly concerning accidents caused by unwanted charge accumulations and the harnessing of electrostatic energy generated during triboelectrification by flow. Despite the growing interest in this field, additional investigations are needed to further elucidate the causes of this phenomenon. The research in this work aimed to analyze the behavior of electrostatic charge acquired by liquids during flow through a polytetrafluoroethylene (PTFE) capillary tube. It was observed that an excess of positive charges were recorded in all liquids, and there was a linear increase in the acquired charge as a function of the drained volume. Aqueous solutions with pH variation did not showed significant differences in charge gain. Alcohols also exhibited an increasing behavior of acquired charge with respect to the length of the carbon chain, except for methanol. Surfactants showed significantly lower charges compared to solutions with varied pH and alcohols. The study measured the electrostatic potential of the tube and observed a sudden decay to -400 V when the flow was stopped. Additionally, composites based on exfoliated and reassembled graphite were used as electrodes to compose a flow sensor. A study was conducted on different types of electrodes to assess their effectiveness in sensing the flow of water and ethanol in a tube. The results demonstrated that using self-powered composites, particularly the two square-face electrodes positioned parallel at 4 mm from the tube, was able to differentiate between the intermittent flow of liquids over several time periods. The system employed an input signal filter and a microcontroller, along with four LEDs to indicate the flow and type of liquid. The present results are important on developing electrostatic charge controllers for the safe transport of various liquids and for sensing the flow, which can prevent accidents and waste.